ECONOMIC EFFICIENCY OF MAIZE GROWING TECHNOLOGIES IN THE CONDITIONS OF THE WESTERN FOREST STEPPE OF UKRAINE (INNOVATIVE ECONOMY, 2025)
Yashchuk T.S., Solyan M.Ya., Dovhan O.M. ECONOMIC EFFICIENCY OF MAIZE GROWING TECHNOLOGIES IN THE CONDITIONS OF THE WESTERN FOREST STEPPE OF UKRAINEPurpose. The purpose of the work is to conduct an analysis of the economic efficiency of corn cultivation technologies of different intensity in the soil-climatic, economic, business conditions of agricultural enterprises of the Ternopil region in the Western Forest Steppe zone of Ukraine and to forecast the prospects of corn sowing in 2025.Methodology of research. The theoretical basis of the study is the scientific works of domestic and foreign scientists on the technology of corn cultivation. The methodological basis of the study is: general scientific methods (synthesis, analysis, abstraction, comparison, grouping, generalization) – for systematizing the scientific approaches of scientists to the theoretical aspects of the development of the crop production industry, the formation and forecasting of the development of the agricultural market of agricultural products in Ukraine and the world; for forming proposals for optimizing the costs of using elements of corn cultivation technology; graphic – for visualizing the results of the study and their schematic representation; abstract and logical method – for formulating one's own interpretation of the assessment of different in intensity technologies of corn cultivation for grain and the conclusions of the study.To conduct practical experiments and observations, general scientific and special methods were used in accordance with the “Methodological recommendations for conducting field experiments with corn (1980)” and generally accepted methods in crop production; economic analysis was carried out based on the application of the methodology for assessing technology by yield level, production cost per unit of product, profitability per hectare of sown area and efficiency level.Findings. It was established that the economic efficiency of corn cultivation technologies depends on the level of their intensity and is determined by the culture's response to individual agrotechnical methods and their complex application in a single technological system. It has been confirmed that an important indicator of the effectiveness of applied mineral fertilizers is their payment in grain. The difference between the costs of mineral fertilizers in intensive and extensive technology was 16 %, which ensured a yield increase of 3.4 t/ha.The level of productivity is 9.2-12.6 t/ha at the price of corn grain sale on average 8500 thousand/t, provided a profit from 1 ha, respectively 40400–61933 thousand. UAH/ha for extensive and intensive cultivation technologies. Considering the fact that the profitability of products was 137.12 % for the intensive technology, 106.88 % for the extensive technology, and the profitability of sales was 57.82 and 51.66 %, respectively, both technologies "have the right to life".The choice is made by farms, depending on the opportunities and the general strategy of the enterprise's development. Despite economic and climate risks, corn remains one of the most profitable crops on par with soybeans and sunflowers.As a result of consistently high prices for this crop, Ukrainian farmers can plan to increase the area of corn sown in 2025 and hope for an increase in the profitability and payback of grain production, under the conditions of a rational choice of the company's strategy depending on its material and financial support, optimal selection of adaptive agrotechnical means taking into account the conditions of climate change in the Western Forest-Steppe zone.Originality. On the basis of the economic evaluation, the feasibility of using different technologies for growing corn for grain in terms of intensity has been established to realize the productivity potential of the crop with the maximum use of agro-climatic and production resources in the conditions of the Forest Steppe.Practical value. The use of the obtained results will expand the opportunities for farms to find the optimal production strategy for the intensity of corn cultivation technologies, aimed at increasing the efficiency of grain farming in the Western Forest Steppe zone, taking into account climatic, economic, financial and business factors.Key words: cereal crops, hybrid, corn, productivity, quality, competitiveness, profitability.
Keywords: cereal crops; hybrid; corn; productivity; quality; competitiveness; profitability